RELATION BETWEEN SURFACE ICE FLOW AND ANISOTROPIC INTERNAL RADIO-ECHOES IN THE EAST QUEEN MAUD LAND ICE SHEET, ANTARCTICA - マエノ, ヒデオ; フジタ, シュウジ; カミヤマ, コキチ; モトヤマ, ヒデアキ; フルカワ, テルオ; ウラツカ, セイホ; MAENO, Hideo; FUJITA, Shuji; KAMIYAMA, Kokichi; MOTOYAMA, Hideaki; FURUKAWA, Teruo; URATSUKA, Seiho (National Institute of Polar Research, 1995)
P(論文) The polarimetric characteristics of radio-echoes reflected in the Antarctic ice sheet (internal radio-echoes) were investigated to clarify the relationship between the preferred orientation of ice crystals and the polarization of electromagnetic waves. The radio-echo sounding was carried out with an 179MHz radio-echo sounder at 14 different sites along the oversnow traverse route from Syowa Station to Dome Fuji in the distance of about 1000km roughly along the flow line in the Shirase Glacier drainage. The A-scope data were obtained at each site from 16 different orientations of the transmitting and receiving antennae, kept parallel to one another. The internal radio-echoes reflected were found to be strongly polarized. In addition, a good correlation was found between the measured surface flow vectors and the orientation dependence of the attenuation. That is, the antennae orientations that give the maximum attenuation are always parallel to the flow line. Moreover, the differences between the maximum and minimum values of the attenuation coefficient at each site are proportional to the flow velocity. These results suggest that polarimetric radio-echo sounding (PRES) is applicable to a technique as follows : 1) to measure approximate flow vector; 2) to investigate deeper layers by orienting the antennae perpendicular to the flow line; and 3) to investigate the dynamics around the summit of the ice sheet. departmental bulletin paper